2014
DOI: 10.1037/hea0000050
|View full text |Cite
|
Sign up to set email alerts
|

The influence of social adjustment on normative and risky health behaviors in emerging adults with spina bifida.

Abstract: Objective To understand the rates of normative and risky health behaviors and the influence of prior and current social adjustment on health risk behaviors in emerging adults with spina bifida (SB). Method These data are part of a larger longitudinal study of youth with SB; at ages 18–19, 50 emerging adults with SB and 60 typically developing (TD) youth participated. Social adjustment was measured at ages 12/13, 14/15, 16/17, and 18/19. Substance use and sexual activity were self-reported by emerging adults.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…They tended to eat less fruit, vegetables and milk or milk products and drank more often sweetened soda. These results were similar to those of studies done by Soe et al and Murray et al (39,40).…”
Section: Health and Well-being -Comparison Of Aspects Of Health And Wsupporting
confidence: 93%
See 1 more Smart Citation
“…They tended to eat less fruit, vegetables and milk or milk products and drank more often sweetened soda. These results were similar to those of studies done by Soe et al and Murray et al (39,40).…”
Section: Health and Well-being -Comparison Of Aspects Of Health And Wsupporting
confidence: 93%
“…Murray et al (40) found in their study of young adults with SB that they reported similar frequencies of cigarette use compared to their peers but less frequent alcohol use, or similar to the results in this study. According to the DASS 16% of the participants in the current study scored moderate to severe for depression.…”
Section: Health and Well-being -Risk Factors For Developing Lifestylesupporting
confidence: 88%
“…Regarding educational and vocational outcomes, 41-56% of young adults with spina bifida go to college compared with 66% of typically developing young people 131, 156, 163, 164. Moreover, recent studies report that only 36-48% of individuals with spina bifida are in full- or part-time employment 131, 159, 164166, significantly lower than the rates in typically developing young people (e.g. 75%; 163, 164, 167) and in those with other chronic conditions (e.g.…”
Section: Quality Of Lifementioning
confidence: 99%
“…75%; 163, 164, 167) and in those with other chronic conditions (e.g. 68-78% in asthma or cancer; 159, 168). Moreover, half of those with spina bifida who work have part-time positions and, thus, their annual salary is below the national average 131.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Social adjustment is a continual quantity like physical, emotional, and intellectual growth. It gradually becomes perfect, which is naturally obtained within experiences (5). Brown (6) refers to social adjustment as a process within which interpersonal and intergroup relationships as well as cultural elements are in a favorable condition.…”
Section: Introductionmentioning
confidence: 99%